2013
DOI: 10.1007/s00431-013-2215-0
|View full text |Cite
|
Sign up to set email alerts
|

Symptom positivity is essential for omitting biopsy in children with suspected celiac disease according to the new ESPGHAN guidelines

Abstract: The aim of this study was to assess the accuracy of serological tests in combination with clinical symptoms for diagnosing celiac disease (CD) according to the new proposed European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) criteria. We retrospectively assessed children and adolescents aged 16 months -19 years who were examined for suspicion of CD (n = 345). Evaluation of clinical symptoms and the presence of tissue transglutaminase (anti-TG-IgA) and endomysial antibodies (EMA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
5
30
0
1
Order By: Relevance
“…Although a single biopsy may be sufficient to establish the diagnosis, different biopsies from various sites (at least four) are ideal to improve diagnostic accuracy and reduce false‐positive and false‐negative results . Guidelines by the European Society of Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) indicate that symptomatic individuals with high IgA‐tTG titers (>10 times the upper normal limit) in patients with human leukocyte antigen risk factors may not require intestinal biopsy . In our center, we recommend biopsies from different duodenal locations (two from the bulb and four from the second portion of the duodenum) and separation of the specimens in different paraffin blocks.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Although a single biopsy may be sufficient to establish the diagnosis, different biopsies from various sites (at least four) are ideal to improve diagnostic accuracy and reduce false‐positive and false‐negative results . Guidelines by the European Society of Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) indicate that symptomatic individuals with high IgA‐tTG titers (>10 times the upper normal limit) in patients with human leukocyte antigen risk factors may not require intestinal biopsy . In our center, we recommend biopsies from different duodenal locations (two from the bulb and four from the second portion of the duodenum) and separation of the specimens in different paraffin blocks.…”
Section: Discussionsupporting
confidence: 45%
“…[45][46][47] Studies from different Brazilian regions have shown a wide frequency range of GI manifestations in patients with T1DM and CD (38.3%-80.0%). [12][13][14][15][16][17]30 In the present study, almost two-thirds of patients (71.4%) with biopsy-proven CD reported unspecific GI 21,49 In our center, we recommend biopsies from different duodenal locations (two from the bulb and four from the second portion of the duodenum) and separation of the specimens in different paraffin blocks. In our population, the samples obtained from different parts of the duodenum during intestinal biopsies was able to identify CD in 79.0% (49 CD out of 62 biopsies).…”
Section: Resultsmentioning
confidence: 96%
“…The number of spared biopsies seems to be lower than that predicted by previous studies,5 11 probably because we applied the new ESPGHAN/BSPGHAN guidelines in a restricted way, considering as symptomatic only those cases with diarrhoea, weight loss, failure to thrive, and/or iron deficient anaemia. This cautiousness in the application of the new ESPGHAN/BSPGHAN guidelines was motivated by a lack of validation of the new diagnostic algorithm by prospective studies.…”
Section: Discussionmentioning
confidence: 64%
“…The specificity of serological tests in asymptomatic individuals was much lower (67%), and it is, therefore, always necessary to perform a biopsy. [35] In a retrospective, multicenter study in Spain, the authors concluded that biopsy could be omitted in 50% of symptomatic patients without a risk of overdiagnosis (100% specificity), while in asymptomatic patients, regardless of serology, a biopsy was mandatory [36].…”
Section: Diagnosismentioning
confidence: 99%